My culture soothes - María Camila Pinzón-Segura; Karen Daniela Rodríguez-Zúñiga (BMJ Paediatrics Open)
In the poignant words of a 12-year-old indigenous girl from the Pijao ethnicity (Tolima, Colombia), who shared her perspective before succumbing to leukaemia, we gain a profound understanding of health from her unique cultural viewpoint. Growing up in El Escobal, indigenus community, with her sister, she experienced the spiritual strength and unity that their culture attributes to twins. For her, health was deeply intertwined with the traditions and rituals of her people, emphasising the healing powers of plants and spiritual harmonisation.She observed a stark contrast between indigenous and Western perspectives on medicine and spirituality. In her reflection, the young girl highlighted the universal language of mutual learning and support that transcends cultural differences. Her message underscores the importance of cultural harmony and the healing power of shared human experiences, advocating for a world where diverse beliefs and practices contribute to collective strength and understanding.This text was her response to the question, 'What is health?' as part of one of the methodological exercises in the doctoral research of Pinzón-Segura MC. Teoría del Intersticio Afectivo: Un nuevo enfoque feminista decolonial de análisis de políticas públicas [Internet]. Bogotá: Repositorio virtual de la Universidad Nacional de Colombia; 2024. The thesis, awarded with the distinction of summa cum laude, included various methods such as participant observation, sociological interviews, and discourse analysis of government documents. The question 'What is health?' specifically guided 40 creative narrative workshops, which were an integral component of the ethnography and arts-based research design.